Consumer Motivation And Concern Factors For Online Shopping In Turkey - Ceren Topaloğlu, Ceren Topaloğlu (Asian Academy of Management (AAM), 2012)
Understanding consumer behaviour in online environments is the basic factor to build an effective consumer-retailer relationship structure. The purpose of this study is to explore the influences of different values and concerns affecting search and purchase intentions of consumers and to build an integrated model, which could explain the purchase intentions of consumers in Turkey, where the majority of the population is under the age of 30. An integrated model of motivation and concern factors on the online shopping is developed to test the causal effect variables. Current study points out that hedonic value is a determinant of the consumer intention to search and purchase. Search intention has a direct impact on purchase intention. Utilitarian value does not have a significant impact on the search intention but it does have an important impact on the purchase intention. From the concern factors perspective, security has a significant impact on both search and purchase intentions, whereas there is no impact for privacy.